Study on the Current Challenges and Solutions in Adolescent Family Education - Liu, Yanlin (International Journal of Social Sciences and Public Administration, 2024)
This paper examines the key challenges in adolescent family education, drawing from both domestic and international research. Through comparative and literature analysis, it explores the differences in family education approaches across various cultural and socioeconomic contexts, highlighting their profound impact on adolescent development. The findings reveal significant disparities in educational concepts, practices, and content, especially between urban and rural areas, as well as among families with varying parental education levels. To address these challenges, the paper proposes strategies to strengthen school-family collaboration, enhance parents’ educational competencies, and improve the family education environment. These strategies aim to foster the holistic development of adolescents’ physical and mental well-being. The study offers valuable insights for educators, policymakers, and researchers in the field of adolescent education.